The Significance Of Social Capital In Intergenerational Social Mobility Of Former Indian Plantation Based Communities: A Case Study Of The Matang Plantations. - D. Wilson, Pearl Sheila (2009)
This thesis presents a micro-sociological study of socio-cultural consequences of the changing landscape of the Malaysian plantation that have undergone significant development and restructuring. Tesis ini meneliti kesan sosio budaya, terhadap penstrukturan fabrik sosial komuniti pekerja ladang yang mengalami perubahan status dari segi hartanah, pengurusan dan bahan pengeluaran secara sosiomikro